Before the Rio Games: A retrospective evaluation of the effects of the population size, GDP and national temperature on winning medals at the 2012 London Olympic Games - Soós, I.; Flores Martinez, J. C.; Szabo, A. (Journal of Human Sport & Exercise, 2017)
Just weeks before the Rio 2016 Olympic Games, this work examined the connection between winning Olympic medals at the London 2012 Games and the participating nations' population size, Gross Domestic Product Per Capita (GDP-PC), and average annual temperature as based on the 'demographic-', 'economic-', and 'geographical' hypotheses (Hoffmann et al., 2002). The three dependent measures jointly accounted for 45% of the variance in winning Olympic medals (p < .001; effect size = 0.82). The contribution of the GDP-PC was relatively moderate (11%). The largest proportion of the variance in winning Olympic medals was explained by the nations` population size (27%). The average national temperature has accounted for a small portion of the variance (7%). Accordingly, the average temperature and GDP-PC had statistically significant, but modest roles in winning medals during the London Games, while the influence of the nations` population size was high. The three measures examined have explained nearly half of the total variance accounting in winning Olympic medals in London.